Self-Directed Learning Beliefs, Readiness and Utilization of E-Learning Technologies among Engineering Educators in a Malaysian Private University - Zakaria, Asmah (2008)
The utilization of E-learning among engineering educators in Malaysia has not been fully investigated. Thus, the two main objectives of the study were to determine utilization of E-learning technologies among engineering educators and to establish relationships between the independent variables and utilization of E-learning technologies. The independent variables were selected demography variables (age, teaching experience, academic qualifications, specialization areas, computer and Internet experience), self-directed learning beliefs (educators’ beliefs, beliefs about students’ learning and facilitation beliefs) and readiness in using E-learning technologies (educators’ readiness, students’ readiness and organizational readiness). This survey research used a Likert-like instrument comprised of questions designed to obtain response on self-directed learning beliefs, readiness, utilization of E-learning technologies and selected demography variables. The population for the study was 580 engineering educators teaching at Universiti Kuala Lumpur. A sample of 165 respondents was selected using stratified sampling among engineering educators teaching at all institutes of Universiti Kuala Lumpur, with the exception of UniKL-Royal College of Medicine. A total of 119 completed questionnaires were returned and used for analysis giving a 72.2 percent response rate. Findings from the study revealed that engineering educators were average users of E-learning technologies. Using Pearson correlation analysis, significant relationships were found between teaching experience, computer and internet experience and utilization of E-learning technologies. There was no significant relationship between age and utilization of E-learning technologies. ANOVA analysis indicated significant mean differences between different academic qualifications and utilization of E-learning technologies, while specialization areas were not statistically significant. Significant relationships were also established for educators’ beliefs, beliefs about students’ learning, facilitation beliefs, educators’ readiness, students’ readiness and organizational readiness. Multiple regression analysis indicated that these variables contributed 40.7 percent of the variance in utilization of E-learning technologies. The most significant predictors in the regression model were educators’ own readiness and educators’ beliefs. While the analyses indicated that there were significant relationships between self-directed learning beliefs, readiness and utilization of E-learning technologies, the results must be interpreted with caution. The average utilization implied that there were other possible reasons for engineering educators’ decisions in utilizing or not utilizing E-learning technologies which the management of the university should investigate. Suggestions for future research include exploring other factors which may influence utilization of E-learning technologies among engineering educators, extending the study to include the students’ perspectives and the implication of the introduction of outcome-based education in engineering education and its implication on utilization of E-learning technologies.